Effect of relative age in the FIFA Women's World Cup U-20 and senior elite categories: differences in playing positions and obtained results - Becerra-Patiño, B. A.; Escorcia-Clavijo, J. B. (Journal of Physical Education and Sport, 2023)
Introduction: The concept of age plays a determining role in high-performance sports, specifically in international tournaments where the participating athletes are categorized by age. An example of this is the women's under-20 world cup. Likewise, the players' ages vary among the national teams in the senior elite world cup. Objective: For this reason, the objective of the present study was to determine the effect of age on the results obtained by each national team and the existing differences between playing positions. Method: The study included 4190 players distributed as follows; U-20 category (n:1344) corresponding to 2014, 2016, 2018, and 2022 World Cups and the senior elite category (n:2846) corresponding to the World Cups between 1991-2019. Quantitative approach study, descriptive type. The statistical treatment was carried out using the program ® version 4.1.0. Univariate and bivariate analysis tests, normality tests, and the Kruskall-Wallis test. Results: The results indicate that, in the senior elite category World Cups, there are statistically significant differences between the teams that become champions (p=0.03) and the teams that finish their participation in the group stage (p=0.00) and occupy the fourth place (p=0.00) in the World Cups, being the champion teams with a higher average age. Likewise, statistically, significant differences were found between age and positions, with goalkeepers having a higher mean age compared to defenders (p=0.00), forwards (p=0.00), and midfielders (p=0.00). As for the U-20 World Cup, given its category, no differences were found between age and playing position. Statistically significant differences were only found between the teams that placed third, with a higher mean age than those in the groups (p=0.00) and quarterfinals (p=0.02). Conclusion: Thus, the variables studied in this study show that age in relation to the results achieved reflects statistically significant differences, both for the U-20 and senior elite categories. Likewise, for the senior elite category, it was found that the first, subchampion, and third place teams have a higher average age than those that finished in the group stage. Finally, also in the analysis of the senior elite category, differences were found between positions, with the goalkeepers having a higher average age than the rest of the field players.